Reingeniería de procesos en el área de la secretaría académica de la facultad de ciencias de la Universidad Nacional de Piura, 2010 - Soto Abanto, Segundo Eloy (2016)
This research tries to redesign the process of critic activities in the Academic Secretary of Science Faculty of Universidad Nacional de Piura, as propose a kind of strategies for improvement different kind of services offered in this area This research was started because of within studies into the Universidad Nacional de Piura showed that customers were much unsatisfied with the received services in Academic Secretary of Science Faculty. Initially, we did a service diagnostic service taking historic information on hand, doing surveys by internal and external customers for selecting the important problems; using statistic technics for data treatment finding highlights problems like 85% of customers served by Academic Secretary Office were completely unsatisfied.and that the main reason was the time of care. Then we did meetings with responsible employments of attended relation areas involved and analyzing finding out no creation value activities for indicating improvements using information peak technology that generating modifications in critic processes found: processing constancy and bachelor and university degrees, with the aim of reducing their time. Finally we did an forecast evaluation by measure time with a sample technic and simulation model of demand peak scenario and in both case the process time decrease with respect to initial time (by 99.76 % and 48.38 was finally realized % for the processes of certificates and degrees and titles , respectively ) and was demonstrated , using a statistical hypothesis test , the existence of highly significant differences ( p < 0.01 ) between the pre and post after process reengineering .